2013
DOI: 10.1002/ardp.201300214
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of α‐Aminophosphonate Derivatives on a Solid Supported TiO2SiO2 Catalyst and Their Anticancer Activity

Abstract: Syntheses of a new series of biologically potent α-aminophosphonates were accomplished by one-pot Kabachnik-Fields reaction using TiO2-SiO2 as solid supported catalyst under microwave irradiation conditions. The chemical structures of all the newly synthesized compounds were confirmed by analytical and spectral (IR, 1H, 13C, 31P NMR, and mass) data. Their anticancer nature was evaluated by screening the in vitro activity on two human cancer cell lines, HeLa and SK-BR-3. Compounds 4i and 4o showed the best acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 39 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The energy options for effecting the reaction were tried by conventional and microwave heating at 400 W . To optimize the required catalyst quantity for this reaction by 400 W for 15 min was established using different quantities of the catalyst and found that 7.5 mol% was sufficient to catalyze the reaction to obtain maximum product yield (97%) (Table , entries 1–6).…”
Section: Resultsmentioning
confidence: 99%
“…The energy options for effecting the reaction were tried by conventional and microwave heating at 400 W . To optimize the required catalyst quantity for this reaction by 400 W for 15 min was established using different quantities of the catalyst and found that 7.5 mol% was sufficient to catalyze the reaction to obtain maximum product yield (97%) (Table , entries 1–6).…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, Chinthaparthi et al [77] . reported a novel MW‐assisted synthetic route for the preparation of α ‐Aminophosphonates, using titania–silica (TiO2-SiO2) as a heterogeneous solid supported catalysis.…”
Section: Microwave As a Green Approachmentioning
confidence: 99%
“…They have been reported to inhibit enzymes involved in amino acid metabolism, thus having a direct influence on cell functions ( Naydenova et al, 2010 ). Many studies have reported the remarkable activity of α -aminophosphonates as pharmacophores ( Reddy et al, 2012 ; Chinthaparthi et al, 2013 ). These compounds exhibit potent biological properties including as plant growth regulators ( Kafarski et al, 1989 ), antiviral ( Long et al, 2008 ; Chen et al, 2009 ; Singh et al, 2020 ), anti-inflammatory agents ( Sujatha et al, 2017 ; Romero-Estudillo et al, 2019 ), herbicides ( Chen et al, 2015 ), protein inhibitors ( Sienczyk and Oleksyszyn, 2009 ; Wang et al, 2012 ; Moreno-Cinos et al, 2019 ), antitumor/antiproliferative agents ( Gu and Jin, 2012 ; Kraicheva et al, 2012 ; Liu et al, 2017 ; López-Francés et al, 2021 ), and antimicrobials ( Atherton et al, 1986 ; El Sayed et al, 2011 ; Rezaei et al, 2011 ; Sudileti et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%